2021
DOI: 10.1002/14651858.cd014546
|View full text |Cite
|
Sign up to set email alerts
|

Visual or visual-tactile examination to detect and inform the diagnosis of enamel caries

Abstract: Visual or visual-tactile examination to detect and inform the diagnosis of enamel caries (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 177 publications
1
13
0
Order By: Relevance
“…The result of the present study indicated that the application of LC Rinse vastly improved the sensitivity, specificity, and diagnostic accuracy of visual-tactile caries relative to previous reports (Table 4 ) [ 32 34 ]. This can be attributed to the fact that the fluorescent particles infiltrated and illuminated only the porous surfaces of the active lesions, and not sound surfaces, inactive lesions, or developmental hypomineralization, thereby increasing its specificity.…”
Section: Discussionsupporting
confidence: 46%
“…The result of the present study indicated that the application of LC Rinse vastly improved the sensitivity, specificity, and diagnostic accuracy of visual-tactile caries relative to previous reports (Table 4 ) [ 32 34 ]. This can be attributed to the fact that the fluorescent particles infiltrated and illuminated only the porous surfaces of the active lesions, and not sound surfaces, inactive lesions, or developmental hypomineralization, thereby increasing its specificity.…”
Section: Discussionsupporting
confidence: 46%
“…In tactile inspection, the hand is moved actively to detect any anomalies. Tactile inspection is used in a variety of conditional assessments, from quality inspection of manufactured parts to examination of the human body in the medical sector [13,14]. In an industrial context, tactile inspections are found in quality checks for a variety of products including textiles [15], injection-moulded parts [11], hydraulic hoses [16], and car tyres [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent decades, dental caries have remained the most important dental public health issue due to the high level of the affected population worldwide and especially in developing countries [ 4 ]. Dental caries are considered an oral disease and can be reversed if diagnosed in the early stages of enamel demineralization [ 5 ].…”
Section: Introductionmentioning
confidence: 99%